Pengembangan Silabus Bahasa Jerman yang Berorientasi pada Keterampilan Berbahasa di SMA - Tampubolon, Erlika; Situmeang, Marisa; Sihombing, Melica; Syakirina, Azza Akira (J-EDu: Journal - Erfolgreicher Deutschunterricht, 2024)
This research aims to develop a syllabus that focuses on developing German language skills at the Senior High School (SMA) level. In its development, student needs, learning objectives, effective teaching methods, and relevant learning materials must be considered. The development of a German language syllabus must be able to provide opportunities for students to interact actively in German. The proposed syllabus is designed to improve students' abilities in speaking, listening, reading and writing in German, as well as integrating content relevant to everyday life and German culture. Syllabus development methods include literature reviews, consultations with German language experts, and hands-on trials in the classroom environment. The development of this syllabus can increase students' learning motivation and help them achieve the learning targets that have been set. It is hoped that this research can make a positive contribution to German language learning at the high school level, by providing a solid foundation for effective and enjoyable teaching, and a positive contribution to improving the quality of German language learning in high school.